The fabrication of nanoporous hydroxyapatite ceramics - A. Ruksudjarit (2018)
Nanoporous hydroxyapatite ceramic was simply fabricated from nano hydroxyapatite powder and polyvinyl alcohol (as a pore former). The vibro-milling method was used to produce the nano hydroxyapatite composite powder. The powder was then sintered at 1200°C for 3 h. It was found that average porosity of the final product of 64.6±1.4% could be achieved. Open and interconnected pores were obtained with average pore size of less than 100 nm, indicating a nanostructure occurring in the ceramic. In addition, the bending strength of the nanoporous ceramic was measured to be 14.7±3.2 MPa which is practically high for bone repairing applications. © 2008 Trans Tech Publications.